Análisis del tráfico ilegal de fauna silvestre en la provincia Los Ríos y su área de influencia, año 2018 - Corrales Pinyui, Victoria Andreina (2018)
The research project had the goal of evaluating the incidence of illegal trade of wildlife species in the 13 cantons of the Los Rios province, and as well, cantons like Balzar, Santo Domingo, La Maná, or El Empalme that constitute the area of influence. To get to know the species of wildlife being traded, 1898 surveys were applied to a sample of the province population. A general list of wildlife species was obtained highlighting the Psittacidae family, of the class Birds in 100% of the surveys, with 88,2 % the guanta, with 76,5% the iguana, parakeet, monkey, and chipmunk, followed by the turtle with 70,6%, armadillo with 58,8%, 35,3% tigrillo and cusumbo, 29,4% boa and guatusa, parrot with 23,5%, fox with 17,6%, saíno and macaw with 11,8 %. It was analyzed the abundance, use, way of obtainment, and vending places, and it was obtained that the organisms more abundant were the guanta (47), the parrots (22), the monkeys (72), the parakeets (43) and the turtles (58). Among the patterns of use it stood out their use as pets in the majority of the cantons and a few for daily consumption. The way of obtaining wildlife species more common was by gift from a relative or friend, followed by purchasing. The stand-out vending place for these species was the market. It was obtained a predictive model of the more risky areas of illegal trade using ArcMap 10.1. Higher risk areas were found towards the north of Santo Domingo, La Maná, Balzar, Quinsaloma and Ventanas. With lower risk of wildlife trade was Baba, Montalvo and Buena Fé. It was applied a Likert questionnaire to 1898 people of all the cantons to describe the social perception about illegal wildlife trade. According to the discriminating questions, it was indicated ignorance about the types of wildlife, their importance in the ecosystem, as well as knowledge of the institutions that regulate the trade of these species, which are important points to slow down the wildlife trading problem.